The counterfactual rewritten history in Robert Harris' fatherland - Laforteza, Dulcinea R. (2008)
The counterfactual is a form of historical fiction that reverses historical facts and uses them as the material into which created characters and events are embedded. In this study, a text that has been categorized as counterfactual was analyzed using an electric approach, a combination of formalistic, reader-response approaches; an genre criticism. Fatherland is a novel set in 1964 in Germany that emerged victorious in WWII. Fatherland was examined in terms of the kind and amount of counterfact used, possibilities and probabilities, and narrative elements. The analysis shows that fatherland is a counterfactual novel in its entirety. However, be that as it may, the novel fails to emerge as a rich counter-memory. That is, it does not go against the grain of history, that while it does present an alternative concept to a historical fact, it ultimately just present a most probable continuation of the history that it counters.
Keywords: Counterfactual (Logic); Historical fiction, German